TINGKAT PENGETAHUAN DAN SIKAP IBU TENTANG KEJADIAN RUAM POPOK PADA BAYI - Sugiarti Sugiarti (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Diaper rash, also called diaper dermatitis, is a skin disorder (skin rash) that results from inflammation in diaper-covered areas, namely in the genitals, around the anus, buttocks, folds of the thighs and lower abdomen. This disease often occurs in infants and toddlers who use diapers, usually at the age of less than 2 years (Tjokronegoro, A., 2000: 19). Based on a preliminary study on April 25, 2017, 10 infants arrived at BPS Zulfiah III Surabaya and as many as 7 babies (69.97%) had diaper rash. Even though diaper rash should not occur in infants. The purpose of this study was to describe the knowledge and attitudes of mothers with the incidence of diaper rash in infants. Method: This study used a descriptive method with quota sampling technique in which sampling was carried out by assigning a number of sample members from June to July 2017 using a questionnaire as a research instrument. Data analysis techniques using frequency tables and cross tabulations with the population are all mothers who came to check their babies at BPS Zulfiah III Surabaya. Results: Based on the results of the study found mothers with good knowledge (17.5%), sufficient knowledge (32.5%) and insufficient knowledge (50%). Whereas from attitudes obtained strongly agree (7.5%), agree (20%), disagree (25%) and strongly disagree (47.5%) Discussion: It can be concluded from this study that mothers who have lack of knowledge, the majority of their babies experience diaper rash. This is influenced by the mother's ignorance about how to properly care for the baby. Health workers are expected to be able to provide information about how to care for babies properly so that diaper rash does not occur in infants.